난치성 반복각막진무름에서 엔디야그레이저 전측각막실질 미세천자술 - 김서영; Seo Young Kim; 고병이; Byung Yi Ko (Daihan angwa haghoi jabji, 2015)
목적: 난치성 반복각막진무름 환자에서 Nd:YAG 레이저를 이용한 전측각막실질 미세천자술의 임상결과를 알아보고자 하였다. 대상과 방법: 본원에서 반복각막진무름으로 진단받고 보존적 치료에 효과가 없는 환자를 대상으로 Nd:YAG 레이저를 이용한 전측각막실질 미세천자술을 시행하였고 최소 4개월 이상 경과관찰이 가능하였던 8명 10안을 연구 대상으로 하였다. 각막미란의 원인과 유병기간, 레이저 치료의 횟수 및 에너지, 수술 전후의 최대교정시력, 안압, 합병증, 치료 후 재발 유무 등을 조사하였다. 결과: 평균 추적관찰 기간은 9.6개월이었다. 레이저 시술은 0.2 mJ 또는 0.3 mJ의 강도로 평균 6.2 mJ의 총 에너지를 사용하였고,대상안 10안 중 2안에서는 두 번의 치료를 시행하였다. 술 후 모든 대상안에서 각막진무름이 소실되었고, 경과관찰 동안의 재발이 없었다. 모든 환자에서 술 후 시력의 유지 또는 호전을 보였고, 경도의 각막혼탁 이외의 다른 합병증은 관찰되지 않았다. 결론: Nd:YAG 레이저 전측각막실질 미세천자술은 난치성 반복각막진무름의 치료에서 단기적으로 효과적이고, 안전한 방법으로 생각한다. <대한안과학회지 2015;56(3):331-338> Purpose: To evaluate the clinical results of anterior stromal puncture (ASP) using neodymium:yttrium-aluminum-garnet (Nd:YAG) laser for refractory recurrent corneal erosion (RCE). Methods: Ten eyes of eight patients with RCE showing poor response to conservative therapy who were treated with Nd:YAG laser ASP and followed up for at least 4 months were studied. The cause and duration of erosions, times, and total energy of the laser were recorded. The preoperative and postoperative best corrected visual acuity (BCVA), intraocular pressure, complications, and recurrence were reviewed. Results: The mean follow-up time was 9.6 months. The laser energy setting was 0.2 or 0.3 mJ per shot. The average total laser energy was 6.2 mJ. Two of 10 eyes received another Nd:YAG laser treatment. All 10 eyes were successfully treated and had no recurrence after the operation during follow-up. Postoperative BCVAs were equal to or better than the preoperative BCVAs. No significant complications except faint corneal haze were observed. Conclusions: Nd:YAG laser ASP is an effective and safe procedure to treat refractory RCE in short-term follow-up. J Korean Ophthalmol Soc 2015;56(3):331-338